ANALISIS DUPONT PADA KINERJA KEUANGAN PERUSAHAAN PEMBIAYAAN KENDARAAN BERMOTOR DI INDONESIA - Riza Praditha (Jurnal Bisnis dan Kewirausahaan, 2016)
The aims of this research are: (1) analyze the influence of the Net Profit Margin toward Return On Asset; (2) analyze the influence the Assets Turnover toward Return On Asset. This research uses secondary data that comes from the financial report 10 of the 61 listed finance companies in Indonesia stock exchange and the Association of finance companies Indonesia with total assets above 1 trillion rupiah. Research was done from July to September 2014. Regression Linearity Method of SPSS (statistical product dan service solution) was used to analyze the data. The results show that: (1) Net Profit Margin Ratio had positive and significant effect toward Return On Asset Ratio; (2) Total Assets Turnover ratio had positive and significant effect toward Return On Asset Ratio This means that the higher level of the profit margin and assets turnover will increase Financial performance of Multifinance Company.